Cypselar anatomy of five species of the tribe Calenduleae, family Asteraceae (Journal of Bangladesh Academy of Sciences, 2015)
Detailed anatomical features of cypselas of five species (Calendula arvensis L., Calendula maderensis DC., Calendula stellata Cav., Calendula suffruticosa Vahl ssp. suffruticosa and Osteospermum vaillantii (Decne.) Norl.) of the tribe Calenduleae have been studied to observe the variation pattern among them. Among the five cypselas, in case of C. stellata, mesocarpic region is made up of only parenchyma cells, containing pits. In remaining four cypselas, mesocarpic region is made up of both parenchyma and sclerenchyma cells. In the cypsela of O. vaillantii, vallecular cavity is present in mesocarpic region. This cavity is absent in remaining four cypselas. In the cypsela of C. arvensis and C. suffruticosa, secretory duct exists in mesocarpic region, which is absent in remaining three cypselas. In the cypsela of C. arvensis and C. maderensis, six vascular traces are present in mesocarpic region, whereas in O. vaillantii, eight vascular traces; in C. stellata, five vascular traces; in C. suffruticosa, four vascular traces are present in mesocarpic region. Based on the above mentioned anatomical features, an artificial key to the species has been constructed.Journal of Bangladesh Academy of Sciences, Vol. 39, No. 1, 65-71, 2015